193k views
2 votes
How is the graph of Y = log(x) transformed to produce the graph of Y = log(2x)+3?

1 Answer

0 votes

Answer:

The required transformation is
X = 2x *10^(3) and Y = y

Explanation:

Transformation means we need to shift the origin to a new position.

Sometimes we also needs to rotate the axis es through some angle.

We need to find the transformation so that, log(X) = log(2x)+3.


log(X) =  log(2x)+3\\ log((X)/(2x)) = 3\\(X)/(2x) = 10^(3) \\X = 2x *10^(3)

Hence the transformation will be
X = 2x *10^(3) and Y = y.

User Martianwars
by
5.4k points